2010
DOI: 10.1159/000265552
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Is Associated with Increased Rate of Cognitive Decline in Questionably Demented Elderly

Abstract: Background: This study examines whether the association of diabetes with the rate of cognitive decline varies according to dementia severity. Methods: Longitudinal study on subjects residing in nursing homes and assisted living (n = 342). The Mini Mental State Examination (MMSE) was used to measure the rate of cognitive decline in diabetic and nondiabetic subjects who were nondemented (Clinical Dementia Rating, CDR = 0; n = 125), questionably demented (CDR = 0.5; n = 58) or frankly demented (CDR ≧1; n = 89) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 86 publications
3
47
0
1
Order By: Relevance
“…In both the Rotterdam Study [30] and the Honolulu Asia Aging Study [31], cases of diabetes identified by screening, i.e., those with no prior history of diagnosis and, therefore, presumably a shorter period of exposure, were not associated with elevations in dementia risk, consistent with our findings. Our finding of a non-significant effect of prevalent diabetes on the rate of decline was also partially consistent with a previous study reporting no such association among non-demented or frankly demented individuals [32]. Our results also suggest that the effect of diabetes on dementia risk and cognitive function is largely independent of other cardiovascular disease risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…In both the Rotterdam Study [30] and the Honolulu Asia Aging Study [31], cases of diabetes identified by screening, i.e., those with no prior history of diagnosis and, therefore, presumably a shorter period of exposure, were not associated with elevations in dementia risk, consistent with our findings. Our finding of a non-significant effect of prevalent diabetes on the rate of decline was also partially consistent with a previous study reporting no such association among non-demented or frankly demented individuals [32]. Our results also suggest that the effect of diabetes on dementia risk and cognitive function is largely independent of other cardiovascular disease risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…Comorbid conditions have been associated with dementia [48]; for instance, diabetes is associated with an increased rate of cognitive decline [49]. As discussed in the Results section, in the pcb-Cohort correlations with comorbidities were likewise evident, and there was a significant correlation with GID.…”
Section: Discussionmentioning
confidence: 83%
“…[3][4][5][6][7] Despite this, there is not clear evidence that the rate of decline in cognitive function is accelerated among individuals who have T2DM, with some reporting no difference 4,8,9 and others reporting accelerated rates of decline. 10,11 Using data from an annual battery of cognitive tests administered to a large cohort of women who participated in a trial of postmenopausal hormone therapy (HT), we investigated the longitudinal patterns of relative deficits in domainspecific cognitive assessments among women with T2DM. We then examined whether T2DM was associated with an increased rate of cognitive decline across up to 7 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%